Effects of biathlon specific fatigue on shooting performance - Sattlecker, G.; Finkenzeller, T.; Buchecker, M.; Gressenbauer, C.; Müller, E.; Lindinger, S. J. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Biathlon is a complex winter sport combining XC skiing and rifle shooting in 5 shot clips. Race results are determined by skiing time, shooting accuracy and shooting time (Hoffman et al., 1992). Physical exercise is considered to influence shooting performance and accuracy (Hoffmann et al., 1992). It is also reported that fatigue leads to an increase of shooting times (Groslambert et al., 1999) as well as a decline of postural control and rifle stability (Hoffman et al., 1992). Furthermore, physical load was found to negatively impact the constant rifle pressure in the shoulder. Aim of the current study was to identify sub-sets of interrelated factors from a large amount of biomechanical variables and to discover predictors for the shooting performance with and without physical stress.